2020
DOI: 10.1002/ctm2.52
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status and related influencing factors of COVID‐19 survivors in Wuhan, China

Abstract: Much research work has been done for hospitalized COVID-19 patients, mainly in clinical characteristics. 4 However, few studies have reported the post-discharge follow-up status, especially the mental health status of COVID-19 survivors. Therefore, in this descriptive case series, we enrolled a large number of COVID-19 survivors in Wuhan, China. We aimed to report the post-discharge mental health status of these survivors and explore relevant influencing factors.This study was conducted in Wuhan Jinyintan Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 4 publications
8
51
3
3
Order By: Relevance
“…The mental health impact of surviving COVID-19 is enormous, and previous studies have reported that psychological distress, anxiety, and depression are widespread among COVID-19 survivors [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mental health impact of surviving COVID-19 is enormous, and previous studies have reported that psychological distress, anxiety, and depression are widespread among COVID-19 survivors [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to coping with the debilitating acute effects of COVID-19, survivors experience a range of mental stressors whilst in-hospital and after discharge. We and others [ 48 , 49 ] have observed a high-level of self-reported symptoms of depression among survivors. Infection-triggered cytokine dysregulation and the neurotropic potential of SARS-CoV-2 have widely been speculated to induce psychopathological sequelae among patients, consistent with neuroinflammatory mechanisms implicated in other psychiatric disorders.…”
Section: Discussionmentioning
confidence: 86%
“…Participants were COVID-19 patients in three studies ( Hao et al ., 2020 ; Wu et al ., 2020a ; Zhao et al ., 2020 ) and surveys were targeted at specific poulations in a further three: pregnant women ( Wu et al ., 2020b )), neurosurgeons ( Sharif et al ., 2020 ) and university students ( Kaparounaki et al ., 2020 ). The study by Wu et al .…”
Section: Resultsmentioning
confidence: 99%